Investigation on Mechanical Strengths and Carbon Foot Print of Modified Foamed Concrete - Koh Heng Boon, Koh Heng Boon; Mohd Jaini, Zainorizuan; Tan Tee How, Tan Tee How (uthm, 2023)
This paper describes the work of a study carried out to investigate the mechanical strengths and carbon foot print of foamed concrete incorporating with local industrial wastes. Experiments were performed to obtain a minimum 28 days compressive strength of 15 MPa modified foamed concretes by using palm oil fuel ash (POFA) and fly ash (FA) as partial cement replacement and unprocessed rush husk ash (RHA) as partial fine aggregate replacement. Carbon footprint analysis was carried out by determining the CO2 emission for each constituent materials in the modified foamed concrete mixes. Although incorporation of POFA in the foamed concrete containing RHA fine aggregate gained lower mechanical strengths compared to the use of FA, the minimum compressive strength is still can be attained. In terms of the sustainability, modified foamed concrete with 30% POFA or 30% FA was found an encouraging reduction of carbon foot print up to about 30% compared to the control foamed concrete. Based on eco-strength indicator, the optimum foamed concrete mix with POFA was found to be at 22.5% cement replacement level. The eco-modified foamed concrete has good potential in civil engineering construction and environmentally friendly.